1991
DOI: 10.1111/j.1532-5415.1991.tb02869.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Postural Hypotension at Baseline in the Systolic Hypertension in the Elderly Program (SHEP) Cohort

Abstract: Somewhat different persons were defined as having PH based upon the 1 minute and 3 minute standing measures of BP, and prevalence estimates of PH can vary depending on whether one or more intervals of measurement are used. Cross-sectional data analysis indicated that PH, in healthy community-dwelling older persons with ISH, may not be associated with a history of disorders or problems usually thought to be related to PH. However, prospective data are needed to determine the prognostic significance of PH, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(86 citation statements)
references
References 11 publications
8
77
0
1
Order By: Relevance
“…[1][2][3]5,6,10,11,13,14 In the current report, lower BMI was positively related to an excess in the odds of OH. Although findings were adjusted for age, hypertension, diabetes, cigarette smoking, total cholesterol, HDL cholesterol, and triglycerides, other unknown comorbidities in leaner individuals are likely to have contributed to this finding.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…[1][2][3]5,6,10,11,13,14 In the current report, lower BMI was positively related to an excess in the odds of OH. Although findings were adjusted for age, hypertension, diabetes, cigarette smoking, total cholesterol, HDL cholesterol, and triglycerides, other unknown comorbidities in leaner individuals are likely to have contributed to this finding.…”
Section: Discussionsupporting
confidence: 56%
“…4,5,8,9,13 In the ARIC study, those with OH were more likely to smoke cigarettes, 1,2 whereas others found no significant relation with smoking. 4,13 In the Korean Health and Genome Study, OH was also unrelated to smoking. If smoking were a factor in Korea, one might have expected a much higher prevalence of OH in men than in women.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations